ANTHOCYANIN EXTRACTION OF RED DRAGON FRUIT PEELS (Hylocereus polyrhizus) USING MACERATION METHOD - Asri Widyasanti; Muhammad Ziauddin Arsyad; Endah Wulandari (BPFP Faperta UNIB, 2021)
Anthocyanins present in the red dragon fruit peel (Hylocereus polyrhizus) can be used as natural dyes. An extraction procedure can be used to acquire anthocyanins. The maceration method was used to isolate anthocyanin dyes in this analysis. The aim of this study was to see how the solvent ratio affected the total anthocyanin content in the skin of red dragon fruit. This research used laboratory experimental method using descriptive analysis. The solvent ratios used were (1:30, 1:40, 1:50 and 1:60) with a mixture of distilled water with 10% citric acid as the solvent. Parameters observed were total yield, pH, residual solvent content, spesific gravity and total anthocyanin content. The best treatment was found to be red dragon fruit peel with a solvent ratio of 1:30, which produced the highest total anthocyanin content of 4.73 mg/L. This treatment resulted total yield 7.40%, residual solvent content 0.05%, spesific gravity 1.30, and pH 1.05, respectively. It was proven that the more solvent added could linearly decrease the effectiveness of anthocyanin extraction of dragon fruit peel extracts.